Vancomycin Resistant Staphylococcus aureus Reported from Tertiary Care Hospital in Nepal - Lama, Urmila; Shah, Dharmendra; Shrestha, Upendra Thapa (Tribhuvan University Journal of Microbiology, 2018)
Objectives: The study was conducted to assess the rate of Methicillin-resistant Staphylococcus aureus (MRSA) among patients and healthcare personnel at Manmohan Memorial College and Teaching Hospital, Kathmandu, Nepal and to evaluate the minimum inhibitory concentration of Vancomycin to MRSA isolates. Methods: A total of 1433 different clinical specimens from patients and 33 nasal swabs from healthcare personnel were subjected to bacteriological investigation following standard protocol. S. aureus were isolated and identified by using standard Microbiological tools. Those isolates were subjected to Antimicrobial susceptibility testing using modified Kirby-Bauer’s disc diffusion method following CLSI guidelines. Results: The rate of S. aureus carriage was found to be 65 (18.9%) in the samples from clinical patients and 24 (72.7%) in the samples from healthcare personnel. The rate of MRSA was found to be 57(85.1%) in patients and 24 (100%) in healthcare personnel. The high distribution of MRSA was found in female of age group 21-30 years (patients: 10.4%; healthcare personnel: 70.8%). Amikacin was found to be most effective antimicrobial. All S. aureus isolates were found to be multidrug resistant (100%). On performing D-test, 10 (17.5%) and 22 (38.6%) of MRSA from clinical specimens showed inducible and constitutive Clindamycin resistance respectively. Whereas, 11 (45.8%) and 4 (16.7%) of MRSA from nasal swabs were found to be inducible and constitutive Clindamycin resistance respectively. Upon performing minimum inhibitory concentration (MIC) test for clinical isolates, 3.5% (2) of MRSA were found to be Vancomycin resistant (VRSA), 54.4% (31) were Vancomycin intermediate (VISA) and 42.1% (24) were found to be Vancomycin sensitive (VSSA). All of the nasal swab MRSA isolates were found sensitive to Vancomycin. Congo red agar method was done for biofilm production. For clinical isolates, 32 (47.8%) were found to be strong, 6 (8.9%) moderate and 29 (43.3%) were non biofilm producer. For nasal swab isolates, 66.7% (16) and 33.3% (8) were found as strong and non-biofilm producer respectively. Conclusion: This study reported the case of VRSA which hasn’t been reported in Nepal. Though present study showed that Vancomycin remains the main choice of treatment of MRSA infection. Therefore, to preserve its value, use of vancomycin should be limited only to those cases where there are clearly needed.